La tarde que late mansa (2019)
This document contains images, text, phrases, and traces of the generative process taken place in the Master of visual arts as well as in the development of it’s research project, a video installation named La tarde que late mansa. The project consists of 2 videos of 5×6 meters presented at irregular intervals between 6 and 30 minutes. The pauses constitute support for the image. The pages of this book recount an experimental exercise about the unnameable whilst inquiring about what can’t be seen or heard but can be perfectly present as a sensation. The 4 chapters of this book are: 1) Introduction 2) A sensation that can’t be named 3) Material/immaterial 4) Visible/Invisible. They bring the reader closer to a search within the visual language about the unattainable and elusive, duration and memory as well as aspects of my experience when relating to the world.